फावथाइ आरो फावथिनायनि बाथ्रा - Baruah, Satya Prasad; Basumatary, Bishweshwar (Bodo Publication Board Bodo Sahitya Sabha, 2015)
Faothai Arw Faothinayni Bathra is a collection of critical articles on Dramatic trends, plays and playwright.
Faothai Arw Faothinayni Bathra
Keywords: Bodo; Theatre; Bodo; Bodo